Risks threatening the health of people participating in mass gatherings: A systematic review - Asghar Tavan; Abbasali Dehghani Tafti; Mahmood Nekoie-Moghadam; Mohmmadhasan Ehrampoush; Mohammad Reza Vafaei Nasab; Hossein Tavangar; Hossein Fallahzadeh (Wolters Kluwer Medknow Publications, 2019)
CONTEXT: Mass gatherings (MGs) are established for different religious, social, political, cultural, and sport motivations. Many risks threaten the participants' health in MGs for different reasons. One duty of health-care system is to identify the risks and manage them to reduce the participants' injuries in MGs. This study aimed to identify and classify the risks threatening the health of participants in MGs and review related articles systematically. SUBJECTS AND METHODS: In this study, we investigated electronic databases including Science Direct, PubMed, Ovid, ProQuest, Web of Science, Scopus, and Google Scholar. This systematic review investigated those health articles which studied MGs published after 2000. Keywords that were searched included (Mass gathering OR Crowd) AND (Assessment OR Evaluation) AND (Disaster OR Emergencies) AND (Injuries OR Stamped). The final full text articles were assessed qualitatively by STROBE article assessment checklist, and then the data extracted from the results of the articles were analyzed and reported. RESULTS: Initially, a total of 1874 articles were found, qualitative exclusion and inclusion criteria were applied, and finally 29 full-text articles were selected for the analysis. More than forty health-related risks were recognized. In order to better understand the risks and use of the results more efficiently, the risks were classified and reported into the following five domains: environmental risks, individual risks, psychological risks, public health risks, and management risks. CONCLUSION: Many risks threaten the health of participants in MGs. Recognizing and managing the risks are considered the primary and basic essentials of health sector for the better management of MGs.